The enhanced expression of estrogen‐related receptor α in human bladder cancer tissues and the effects of estrogen‐related receptor α knockdown on bladder cancer cells. Issue 8 (11th April 2019) - Ye, Xinqing; Guo, Jinan; Zhang, Hongxiang; Meng, Qinggui; Ma, Yun; Lin, Rui; Yi, Xianlin; Lu, Haoyuan; Bai, Xianzhong; Cheng, Jiwen
Abstract: Estrogen‐related receptor α (ERRα) belongs to the superfamily of nuclear orphan receptors. However, the role of ERRα in bladder cancer remains unknown. This study examined the expression of ERRα in bladder cancer tissues and explored the molecular mechanisms of ERRα in bladder cancer progression. The expression of ERRα in bladder cancer tissues from 61 patients was determined by immunohistochemistry. We performed quantitative real‐time polymerase chain reaction assay to detect the gene expression levels and carried out Western blot assay to measure protein levels. In vitro functional assays, including colony formation, Cell Counting Kit‐8, Transwell invasion, and migration assays, were performed to detect bladder cancer cell growth, proliferation, invasion, and migration, respectively. Flow cytometry was used to determine the cell apoptotic rate of bladder cancer cells. Among the 61 detected bladder cancer tissues, 39 bladder cancer tissues showed positive ERRα immunoreactivity. Higher ERRα immunoreactivity score was significantly associated with TNM stage, tumor grade, distant metastasis, and poor survival in patients with bladder cancer. Univariate and multivariate analyses showed that ERRα immunoreactivity was an independent prognostic factor for overall survival in patients with bladder cancer. ERRα was found to be upregulated in bladder cancer cell lines, and knockdown of ERRα suppressed bladder cancer cell growth, proliferation, invasion, and migration; promoted bladder cancer cell apoptosis; and inhibited the epithelial‐mesenchymal transition of bladder cancer cells. On the other hand, bladder cancer cell proliferation, invasion, and migration were significantly enhanced after cells were transfected with an ERRα‐overexpressing vector. In vivo tumor growth and metastasis assays showed that ERRα knockdown resulted in remarkable inhibition of tumor growth and tumor metastasis in nude mice. Collectively, our results suggest that the enhanced expression of ERRα may play a key role in the development and progression of bladder cancer and ERRα may serve as an important prognostic factor for bladder cancer. Abstract : Estrogen‐related receptor α (ERRα) belongs to a class of nuclear orphan receptors. However, the role of ERRα in bladder cancer remains unknown. The data from the present study suggest that the enhanced expression of ERRα may play a key role in the development and progression of bladder cancer and serve as an important prognostic factor for bladder cancer.